Zeolite-Based Silica Synthesis With Calcination Temperature Variations 100oC, 150oC and 200oC - Helisa Duwi Maesari; Misfalakhul Hidayah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
This research on Zeolite-Based Silica Synthesis with Calcination Temperature Variations 100 , 150 , and 200 . The purpose of this study was to determine the effect of calcination temperature on the silica structure contained in zeolites. Synthesis is made from zeolite, NaOH and HCl by sol-gel method and temperature calcination treatment 100 , 150 , and 200 . Zeolite samples were characterized by XRD (X- Ray Diffraction). The results showed that sample A with temperature 100 contains Quartz silica, moganite silica (SiO2), and Aluminum Oxide (Al2O3). Sample B with temperature 150 contains Quartz silica (SiO2), and Anorthite (AlCaO8Si). Sample C with 200 contains Quartz silica and Aluminium Oxide (Al2O3). As for the crystallite size in sample A measuring 678.51 nm, sample B measuring 488.16 nm and sample C measuring 488.13 nm. ©2018 JNSMR UIN Walisongo. All rights reserved.